Biowaste Sago Bark Based Catalyst Free Carbon Nanospheres: Waste to Wealth Approach - Hegde, Gurumurthy; Shoriya Aruni, Abdul Manaf; Kumar, Anuj; Ali, Gomaa A. M.; K. F., Chong; Zainab, Ngaini; K. V., Sharma (ACS Publications, 2015)
Catalyst-free carbon nanospheres were synthesized using simple one-step pyrolysis techniques where biowaste sago bark is used as a carbon precursor. Obtained carbon nanospheres showed a porous nature and revealed that more than 95% carbon is present in the synthesized carbon nanospheres with particle size ranging from 40 to 70 nm. An electrochemical study showed a specific capacitance value of 180 F g−1 at 2 mV s−1 and the cycling stability up to 1700 cycles. Obtained carbon nanospheres are useful in supercapacitor applications. The presented study revealed a waste to wealth approach thereby reducing waste in the environment.